Rekindling the sacred fire for children and families (First Peoples Child & Family Review, 2019)
This video describes the partnership between the Sun Lodge Village and Peguis Child and Family Services in Peguis First Nation, Manitoba. Together we are providing opportunities for families, youth, and children to find their way back to traditional spiritual ways of healing and knowing who they are through ceremony, traditional teachings, and land-based experiences. The story is told through voices, pictures, and songs of the Sun Lodge Village family, child and family service workers, and the parents and youth involved. It describes the need for radical change in the child welfare system for Anishinaabe families, to find alternatives to placing so many children in foster care. It shows how such change is indeed possible through helping families from within traditional Anishinaabe ways of being. Those involved describe how these ways have provided healing for them, how their families have been strengthened, and how special the Sun Lodge and the Sun Lodge Village family have become for them.